ETHICS IN FOCUS: A BIBLIOMETRIC AND CONTENT ANALYSIS OF ISLAMIC BANKING AND FINANCE RESEARCH - Zahari, Siti Aisyah; Shahimi, Shahida; Alma’amun, Suhaili; Ismail, Abdul Ghafar (Bank Indonesia, 2024)
This study performs a bibliometric analysis of the literature on ethics in Islamic banking and finance (IBF) in the Scopus database. A total of 366 scholarly articles pertaining to the subject of ethics in IBF are analyzed using VOSviewer, Wordstats, Harzing’s Publish or Perish and Microsoft Excel. The development of the literature on ethics in IBF is outlined in this study, along with a list of the most significant authors, as well as relevant nations, groups, and journal sources. Moreover, the study identifies six major clusters namely, corporate image and customer loyalty of IBF, ethical decision making in IBF, Islamic work ethics, IBF standards and supervisory, ethical products and services of IBF, and maqasid al-shariah and IBF. The findings show an increasing number of citations and documents related to ethics in IBF whereby, the journal of